Hubungan Model Pembelajaran Cooperative Learning Tipe Index Card Match Terhadap Motivasi Belajar Qur’an Hadist Siswa Kelas VII di MTs Al-Fathimiyah Karawang - Siti Patriah (Jurnal Ilmiah Iqra', 2022)
The Correlation of Cooperative Learning Model Index Card Match Type The Motivation of Learning The Hadith of Class VII Students in Mts Al-Fathimiyah. Choosing a learning model is something that the teacher needs to pay attention to increase student motivation. This study aims to determine the learning motivation of grade VII students using the type of cooperative learning model index card match in the Qur'an Hadits study program at MTs Al-Fathimiyah Karawang. This type of research is a bivariate correlation study (product-moment). The population in this study were all students of MTs Al-Fathimiyah Karawang class VII A and VII B, totaling 74 students, while the study sample was 40 students. Data collection using a questionnaire with as many as 40 questions. The cooperative learning model index card match type greatly contributes to students' motivation to learn the Qur'an Hadith, with 92.6% and 7.4% determined by other variables that have not been studied. There is a significant effect of the cooperative learning model of index card match type on students' motivation to learn the Qur'an Hadith analyzed using the F test statistic with a significance level α (0.05), obtained Fcount = 476.507 and Ftable = 4.10 so that Fcount> Ftable or 476,507> 4,10. So Ho was rejected, and Ha accepted. There is a significant relationship between the learning model of the cooperative learning model type index card match on the students' motivation to learn the Qur'an Hadiths of students who were analyzed using bivariate correlation test statistics, and then the Sig value was obtained. = 0.000 with count = 0.962 and rtable= 0.312 so that Sig. <α (0.05) or rcount> rtable namely 0.000 <α (0.05) or 0.962> 0.312, therefore Ho is rejected and Ha is accepted. From these results, it can be concluded that there is a significant relationship between the type of cooperative learning model index card match with the motivation to learn the Qur'an Hadits of grade VII students at MTs Al-Fathimiyah Karawang